Peran Modal Sosial terhadap Keberlanjutan Pembudidayaan Rumput Laut Menghadapi Perubahan Iklim - Syarif, Asriyanti; Arwati, Sitti; Sartika, Dewi (Jurnal Galung Tropika, 2024)
Climate change is a natural phenomenon that poses a risk of vulnerability in the sustainability of seaweed cultivation because it can reduce production and income. Therefore, a sustainability strategy is needed, as well as the role of social capital, which is the most important element in carrying out cultivation because it is a means to build communication and cooperation in overcoming obstacles from climate change. Social capital is an element that supports internal and external factors. The study's objectives are: (1). The role of social capital in the sustainability of seaweed cultivation (2)—the existence of a sustainability strategy in dealing with climate change. Therefore, the study was conducted by taking the location of the seaweed center in South Sulawesi in Laikang Village, Manggarabombang District, Takalar Regency, by taking 20 informants from the seaweed farming community, extension workers, village government, and the Fisheries and Marine Service. It was done by conducting observation actions and in-depth interviews with the FGD (forum discussion group) mechanism and documentation. Data analysis was carried out descriptively and qualitatively using a Likert scale. The sustainability strategy was compiled with a SWOT analysis by including internal and external factors in the seaweed business involving the farming community and supporting institutions. The study results showed that social capital was built to improve communication and strengthen networks (bonding and bridging). It was based on the norm of getting out of the shocks that arise in seaweed cultivation due to climate change. The strategy that can be applied from the SWOT analysis, namely the existence of partnerships that must be built so that seaweed businesses can be sustainable in facing shocks from climate change by involving local governments, educational research institutions, the Department of Fisheries and Marine Affairs, seaweed farmers, with strengthening financial institutions and markets.